Analisis Kemampuan Representasi Matematis Siswa Kelas II SD pada Materi Bilangan Bulat melalui Studi Kasus - Caroline Rotua Joesputri Samosir; Cantika Sri Agustin; Nur Assyifa Khoirunnisa; Shifa Aulia Sabna; Hafiziani Eka Putri (STKIP Subang, 2026)
Mathematical representation ability is an essential skill that students need to develop in mathematics learning, as it helps them understand, communicate, and solve mathematical problems through various forms of representation. However, students’ mathematical representation ability at the elementary school level still requires further investigation, particularly in learning integers. This study aimed to analyze the mathematical representation abilities of second-grade elementary school students in learning integers through a case study approach. The research employed a descriptive qualitative design using a case study method. The participants consisted of five second-grade elementary school students selected through convenience sampling. Data were collected through written tests, task- based in-depth interviews, documentation, and field notes. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings revealed that students’ mathematical representation abilities varied across indicators. Visual representation was the most dominant indicator, as students were able to use pictures and object grouping to understand multiplication as repeated addition. In symbolic representation, most students were able to translate problems into appropriate mathematical operations, although some still relied on repeated addition before expressing multiplication symbols. Meanwhile, verbal representation required further improvement because not all students were able to explain their problem-solving processes and mathematical reasoning comprehensively. Therefore, the mathematical representation abilities of second-grade elementary school students were generally well developed, particularly in visual and symbolic representations, although verbal representation still needs further enhancement.